Factores que determinan la cooperación con clientes en innovación - Sánchez González, Gloria; González Álvarez, Nuria (Cuadernos de Estudios Empresariales, 2007)
The aim of this paper is to investigate the determinants of R&D cooperation between manufacturing firms and a particular group of external stakeholders: their customers and users. The crux of our analysis are two variables that have been acknowledged in the literature as important factors for this kind of cooperation but that have been studied from a purely theoretical perspective: 1) sticky information (information costly to acquire, transfer and use) and, 2) heterogeneous needs of the market. The present study analyzes deeply these variables and our results confirm that both factors have a significant influence on cooperation with customers. R&D experience, cooperation with other stakeholders, absorptive capacity, product innovation and foreign ownership are also shown to influence on the likelihood of customer cooperation.